REM OBSERVATIONS OF FRACTURE-BEHAVIOR AND CRYSTAL POLARITY OF ZNO SINGLE-CRYSTALS - Peng, L; Czernuszka, J (Publ by IOP Publishing Ltd, 1991)
Low index surfaces of ZnO single crystals have been examined by using reflection electron microscopy (REM). It is found that the fracture behaviour and detailed atomic structures of the (11̄00) and (112̄0) faces of ZnO crystals depend sensitively on the cleavage direction and applied stress. The polar (0001) surface is observed to consist of domains of Zn-terminated and O-terminated faces.